Mass gathering in Qatar 2022 World Cup. What should be especially monitored? - Pedro Llorente-Nieto; Gregorio González-Alcaide; José-Manuel (Elsevier, 2024)
Summary: Objectives: At the end of 2022, the football world championship will be held in Qatar. These types of meetings require a risk analysis. It proposes an approach to determine which health risks should be prioritized. Method: We use a mixed methodology (Hierarchical Process Analysis, World Health Organization STAR and European Commission INFORM) to determine the risk level of a total of 12 health entities. Results: Our analysis identifies 6 health entities with a moderate risk. There are 4 whose valuation is as low risk and 2 as very low. Conclusions: In our work we focus the analysis from a point of view of the route of transmission or presentation of health events, which facilitates a visualization of the preventive measures to be implemented, both organizationally and individually by the attendees.